2014
DOI: 10.1016/j.jacc.2013.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-Dependent Upper Reference Limits for the High-Sensitivity Cardiac Troponin T Assay

Abstract: Objectives To determine the 99th percentile upper reference limit for the highly sensitive cardiac troponin T assay (hs-cTnT) in three large independent cohorts. Background The presently recommended 14 ng/L cutpoint for the diagnosis of myocardial infarction using the hs-cTnT assay was derived from small studies of presumably healthy individuals, with relatively little phenotypic characterization. Methods Data were included from three well characterized population-based studies: the Dallas Heart Study (DHS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
205
2
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 331 publications
(241 citation statements)
references
References 30 publications
21
205
2
13
Order By: Relevance
“…Furthermore, we did not observe any differences in the associations or thresholds of each cardiac biomarker with risk of incident HF in important subgroups. Prior investigations have suggested that thresholds for troponin, for example, may be higher in men (versus women) 32,33 and blacks (versus whites). 33 Interestingly, it has been suggested that NT-proBNP levels may be higher in women (versus men) 34 and blacks (versus whites).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we did not observe any differences in the associations or thresholds of each cardiac biomarker with risk of incident HF in important subgroups. Prior investigations have suggested that thresholds for troponin, for example, may be higher in men (versus women) 32,33 and blacks (versus whites). 33 Interestingly, it has been suggested that NT-proBNP levels may be higher in women (versus men) 34 and blacks (versus whites).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the highly sensitive cTnT ECLIA method, variability among the 99th URL values reported in different studies and by manufacturers is very similar (Table 5) [9,12,26,41,124,[126][127][128]. Considering as a whole the clinical studies including a total of 10,078 individuals [9,12,26,47,124,[126][127][128], median (25th-75th percentiles) values of 99th URL results of highly sensitive cTnT ECLIA method are for the overall population 14.6 (13.2-18.0) ng/L, for men 16.0 (15.0-19.5) ng/L, and for women 12.0 (9.6-12.5) ng/L, respectively.…”
Section: Do Differences In Troponin-dependent 99th Url Values Depend mentioning
confidence: 84%
“…Data reported by Franzini et al [26], for example, show that the calculated 99th URL values for cTnT ECLIA method in apparently healthy elderly men and women (>65 years) were 36.8 ng/L and 28.6 ng/L, respectively, whereas the 99th URL value advocated by the manufacturer is 14 ng/L. Furthermore, Gore et al [41] reported that the use of a uniform 14 ng/L cutoff for the hs-cTnT assay may lead to over-diagnosis of AMI, particularly in men and the elderly.…”
Section: Agementioning
confidence: 97%
“…Troponin elevations with age, contributed in part by age-related co-morbidities, have been emphasized [23][24][25]. Sandoval [9] and Collinson [26] underscore the vital role of population selection and pre-screening on the 99P decision limit.…”
Section: Reference Populationmentioning
confidence: 99%